ANALISIS PENGARUH UKURAN PERUSAHAAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Logam & Sejenisnya yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Rista Bintara (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The purpose of the research is to examine whether institutional ownership, managerial ownership, audit committee, and the size of the company has an effect on earnings management. The type of research used in this study is causal comparative research. The population in this study are companies manufacturing sub-sector of metal and the likes are listed on the Indonesia Stock Exchange Period 2011-2014. The data used is secondary data. Data collection method used is book study method and the documentation. The analysis used is multiple regression analysis. The results showed that: 1) in partial institutional ownership, managerial ownership has effect and significant effect on Earnings Management with a negative direction; 2) partial variable audit committee has effect and significant effect on the Profit Management with a positive direction; 3) partial variable size has no effect and no significant effect on Earnings Management.